Effects of Headache on CNS Vital Signs Performance in a Concussed Community Sample. (26th July 2019) - Moreno, C C; Houck, Z; Svingos, A; Greif, S; Hromas, G; Jaffee, M; Heaton, S; Deming, C; Bauer, R M
Abstract: Purpose: Headache (HA) is the most common symptom following concussion. We examined the effect of HA on CNS Vital Signs (CNSVS) performance. Methods: Data were analyzed from 63 patients (25 males, Mdn age [IQR]=23.0 [21.0], Mdn days since injury [IQR]=66.0 [112.0]) presenting to an interdisciplinary concussion clinic. HA disorders were diagnosed post-injury by a board-certified neurologist and obtained from medical records. Nearly half (51%) of the sample had a HA diagnosis. We analyzed the performance on CNSVS multiple test domains: Composite Memory, Psychomotor Speed, Complex Attention, and Cognitive Flexibility. Chi-square test of independence assessed differences in demographic and medical history factors among those with and without HA diagnosis. Multivariate analyses of covariance assessed the influence of HA on CNSVS multiple test domains. Factors significantly different between groups were added as covariates. Results: There were significant interactions of loss of consciousness (LOC; Χ 2 (1, 63)= 6.22, p=.013), history of attention-deficit/hyperactivity disorder (ADHD; Χ 2 (1, 63)= 5.13, p=.023), and daytime sleepiness (Χ 2 (1, 63)= 6.14, p=.013) among those with and without HA diagnosis. The presence of these medical conditions composed 19%, 28%, and 40%, respectively, of HA diagnoses. There was no statistically significant omnibus effect of HA diagnosis on the four CNSVS domain scores without covariates (F[4, 58]= 0.46, p=.76, ηp 2 =.03) or when controlling for LOC, history of ADHD, and daytime sleepiness (F[4, 55]=0.44, p=.78, ηp 2 =.03). Conclusion: Findings suggest that HA diagnosis is unrelated to performance on CNSVS in individuals after concussion.